Strategi Pengembangan Kapasitas Perawat dalam Pelayanan Kesehatan - Suprapto Suprapto; Rifdan Rifdan; Hamsu Abdul Gani (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; the ability, skills and professionalism of nurses and accountability of health public administration need to be improved in the professional aspect. Destination; review and explain; how is the strategy for developing the capacity of nurses in health services. Methods: qualitative research data collection was carried out by observation, interviews, and document study. Analysis using descriptive qualitative by simplifying data, presenting data, and conclusions and validating the data by triangulating data. Results: shows that the strategy for developing the capacity of nurses in health services can be realized by education and training based on spiritual aspects and technological aspects. Conclusion; that the attitude of nurses through the dimensions of spirituality and technology towards health services to patients continues to be encouraged so that the formation of this new mentality is characterized by a more holistic orientation.